Public perception of littering : Case study in Kota Kinabalu City / Azweynna Khalid and Daud Arshat - Khalid, Azweynna; Arshat, Daud (2011)
Littering is no longer considered as an important issue for some people. Not many countries around the globe have successfully tackled the issue of littering and Sabah is one of them. Littering not only poses serious environmental problem, it also causes losses in terms of business opportunities and foreign investments. The question of why people litter is very difficult to be answered. It has a strong relationship with an individual perception of littering. How people perceive littering differs from one individual to another. This research was an attempt to obtain the people’s perception of littering and focused on Kota Kinabalu city as a case study. A survey questionnaire was developed and distributed to 120 respondents in 12 different areas in Kota Kinabalu. Based on a simple descriptive analysis, the study attempted to gauge the people’s perception of littering based on the factors presumed to be the causes for people to litter. An inferential statistics was also employed to examine the relationship between the people’s perception of littering with their demographic profiles.